2021
DOI: 10.1111/cwe.12361
|View full text |Cite
|
Sign up to set email alerts
|

What Drove Housing Wealth Inequality in China?

Abstract: Although China is experiencing a deterioration in wealth distribution where housing is playing a dominant role, this issue has received scant research attention despite its importance. Combining four rounds of the China Household Finance Survey (CHFS) data, this paper measures and discusses wealth inequality in China, with a special emphasis on the contribution of housing. Our analysis reveals that housing is the largest contributor to wealth inequality, responsible for around 70 percent of total wealth inequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Thus, the more urban population growth inflates the price of housing the more it drives a wedge between housing (and, for that matter, financial) wealth-building prospects of renters and owners (who can access appreciation; path N). Unsurprisingly, we observe large and growing housing wealth disparities across metropolitan space and tenures (Alexandra Killewald & Brielle Bryan, 2016;Di et al, 2007;Wan et al, 2021;Wind et al, 2017). 2 In metropolitan areas that sit atop the urban hierarchy ("superstar cities"), the aforementioned processes can interact to generate endogeneity of selective migration by education, skills and preferences, incomes and housing prices (Gyourko et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, the more urban population growth inflates the price of housing the more it drives a wedge between housing (and, for that matter, financial) wealth-building prospects of renters and owners (who can access appreciation; path N). Unsurprisingly, we observe large and growing housing wealth disparities across metropolitan space and tenures (Alexandra Killewald & Brielle Bryan, 2016;Di et al, 2007;Wan et al, 2021;Wind et al, 2017). 2 In metropolitan areas that sit atop the urban hierarchy ("superstar cities"), the aforementioned processes can interact to generate endogeneity of selective migration by education, skills and preferences, incomes and housing prices (Gyourko et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…The internationalization of financial markets has also boosted speculative demand for housing, especially in the highest‐level urban areas. These forces collectively have produced the widely observed increase in geographic disparities in housing rents and purchase prices (Gyourko et al, 2013; Hochstenbach & Arundel, 2020; Moretti, 2013; Wan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have suggested that house prices may reduce the household wealth gap (Kuhn et al, 2020), this is the opposite case in China. Li and Wan (2015) and Wan et al (2021) show that property value contributes as high as 70% to the wealth gap in China, and the rate is gradually increasing. At the same time, the above studies suggest that the rise in house prices has driven the wealthy class to invest more in property assets, further widening the wealth inequality.…”
Section: Consider Endogeneitymentioning
confidence: 99%
“…The price increases made real estate less affordable, resulting in a gap between those who own real estate and those who do not (Zhang, Sun, and Zhang 2020;Li and Fan 2020). Rising housing wealth was the biggest contributing factor to wealth inequality from 2011 to 2017 and the only driver over 2015-2017 (Wan, Wang, and Wu 2021). 24 This is not surprising given the massive property price increases during that period.…”
Section: Rising Real Estate Pricesmentioning
confidence: 99%
“…The younger generation in particular has found itself excluded from the property market despite their generally better education. 28 As for the effects of rising housing prices on inequality, Wan, Wang, and Wu (2021) find that rising property prices have slightly increased wealth inequality from 2011 to 2017, the latest year covered in their analysis.…”
Section: Rising Real Estate Pricesmentioning
confidence: 99%